PENGARUH BIO-SLURRY DAN FOSFOR TERHADAP PERTUMBUHAN DAN HASIL BUNGA KOL (Brassica oleracea L.) DATARAN RENDAH - Mia Ayu Oktaviani; Usmadi Usmadi (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2019)
Cultivation of cauliflower with bio-slurry and phosphorus fertilizer was done as an effort to improve soil fertility to increase growth and yield of cauliflower. The study was conducted to determine the effect of bio-slurry with phosphorus fertilizer on growth and yield of lowland cauliflower. The experiment was carried out at Agrotechnopark of Jember University screenhouse from February to May 2018. The research method used a Randomized Block Design (RBD) with split plot enviromental design on 3 levels of bio-slurry factor and 4 levels phosphorus factor was repeated 3 times. The first factor was liquid bio-slurry consisting of no bio-slurry; 500 ml bio-slurry / plant; 1000 ml of bio-slurry / plant. The second factor was phosphorus fertilizer (TSP) consisting of 0 g / plant; 1.5 g / plant; 3 g / plant; 9 g / plant. The experimental results showed that the interaction between the bio-slurry dose and phosphorus fertilizer had a significant effect on the yield and quality of the flowers except for the fresh weight of the flower. The treatment of TSP fertilizer affects growth except for chlorophyll content and total leaf area. The bio-slurry treatment can increase the fresh weight of cauliflower.Keywords:cauliflower, bio-slurry and phosphorus